Dataset of ASE and genomic predictors from Capsella grandiflora - Benjamin Laenen (Stockholm University, 2016)
The dataset includes all the information used to assess the importance of genomic predictors on allele specific expression in Capsella grandiflora. The description of the predictors can be found in the Steige et al 2017 PNAS .
Keywords: Evolutionary Biology; 60411 Population, Ecological and Evolutionary Genetics; Biological Sciences; Biologi; Evolutionary Biology; Evolutionsbiologi